Interleukin-26, preferentially produced by TH17 lymphocytes, regulates CNS barrier function. Issue 6 (November 2020) - Broux, Bieke; Zandee, Stephanie; Gowing, Elizabeth; Charabati, Marc; Lécuyer, Marc-André; Tastet, Olivier; Hachehouche, Lamia; Bourbonnière, Lyne; Ouimet, Jean-Philippe; Lemaitre, Florent; Larouche, Sandra; Cayrol, Romain; et al.
Abstract : Objective: To investigate the involvement of interleukin (IL)-26 in neuroinflammatory processes in multiple sclerosis (MS), in particular in blood-brain barrier (BBB) integrity. Methods: Expression of IL-26 was measured in serum, CSF, in vitro differentiated T helper (TH ) cell subsets, and postmortem brain tissue of patients with MS and controls by ELISA, quantitative PCR, and immunohistochemistry. Primary human and mouse BBB endothelial cells (ECs) were treated with IL-26 in vitro and assessed for BBB integrity. RNA sequencing was performed on IL-26–treated human BBB ECs. Myelin oligodendrocyte glycoprotein35–55 experimental autoimmune encephalomyelitis (EAE) mice were injected IP with IL-26. BBB leakage and immune cell infiltration were assessed in the CNS of these mice using immunohistochemistry and flow cytometry. Results: IL-26 expression was induced in TH lymphocytes by TH 17-inducing cytokines and was upregulated in the blood and CSF of patients with MS. CD4 + IL-26 + T lymphocytes were found in perivascular infiltrates in MS brain lesions, and both receptor chains for IL-26 (IL-10R2 and IL-20R1) were detected on BBB ECs in vitro and in situ. In contrast to IL-17 and IL-22, IL-26 promoted integrity and reduced permeability of BBB ECs in vitro and in vivo. In EAE, IL-26 reduced disease severity and proinflammatory lymphocyte infiltration into the CNS, while increasing infiltration of Tregs. Conclusions: Our study demonstrates that although IL-26 is preferentially expressed by TH 17 lymphocytes, it promotes BBB integrity in vitro and in vivo and is protective in chronic EAE, highlighting the functional diversity of cytokines produced by TH 17 lymphocytes.